2018
DOI: 10.12927/hcpol.2018.25547
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Views on Solutions to Improve Health System Performance

Abstract: Overall response rate was 37%. There was considerable consensus on identified solutions to improve the healthcare system. Resistance was observed in two major areas: information systems and changes directly affecting doctors' practice. The groups' positions cannot explain the inability to implement important characteristics of high-performing systems. The findings raise new questions on the actual sources of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…While we anticipated that different stakeholder groups might have opposing views, our data shows that challenges and solutions were generally agreed upon by the different types of stakeholders. This is consistent with another study conducted in Québec that found general agreement between health professionals and decision-makers on solutions to improve the health system [26]. Our study adds to this by mobilizing local citizens as well.…”
Section: Feasibility Of Our Approachsupporting
confidence: 92%
“…While we anticipated that different stakeholder groups might have opposing views, our data shows that challenges and solutions were generally agreed upon by the different types of stakeholders. This is consistent with another study conducted in Québec that found general agreement between health professionals and decision-makers on solutions to improve the health system [26]. Our study adds to this by mobilizing local citizens as well.…”
Section: Feasibility Of Our Approachsupporting
confidence: 92%
“…En plus d'un meilleur contrôle des dépenses, les projets de réforme des systèmes de santé font face à un autre impératif, soit un renouvèlement de l'offre de soins [1]. Alors que les opérations de restructuration décrétées par les gouvernements engendrent des bouleversements importants auprès des acteurs interdépendants du système de santé, elles ne mènent pas toujours à la concrétisation des changements prévus [1][2][3][4][5][6]. Ces constats raniment un intérêt pour l'étude des instruments à la disposition de l'État dans sa gouverne ; ils suscitent des interrogations nouvelles sur les possibilités et les limites des États pour entreprendre et mener des transformations majeures.…”
Section: Introductionunclassified
“…Daniels et al [22] hold that a better understanding of the level of congruence amongst stakeholder perspectives on a healthcare innovation is “ important for addressing tensions between stakeholders and therefore for creating coherent and implementable policy ” (p. 492). Several studies recognise multiple stakeholders as key informants whose differing perspectives may serve as contextual evidence that can inform the development of healthcare policies and practices [2324252627].…”
Section: Introductionmentioning
confidence: 99%